Genome-wide comprehensive analysis the molecular phylogenetic evolution, functional divergence and tissue-specific expression of GH3 gene family in Salvia miltiorrhiza, Arabidopsis thaliana, and Oryza sativa - Wang, Bin; Li, Min; Chen, Jun; Chen, Longtao (Frontiers in Plant Science, 2025)
Auxin, as a central phytohormone and signaling molecule, plays a crucial role in plant growth and development. The activity of auxin is tightly regulated by the auxin-responsive GH3 gene family. In this study, a total of 40 GH3 genes in A. thaliana, S. miltiorrhiza, and O. sativa were identified and subjected to comprehensive study. Phylogenetic analysis revealed that those GH3 genes can be classified into three distinct subgroups, with 11 pairs of paralogs identified. Genetic divergence analysis indicated that the GH3 gene family had predominantly experienced purifying selection as evidenced by the Ka/Ks ratio being less than 1 for all 11 paralogs pairs. Positive selection analysis with the site and branch-site models further suggested that SmGH3 AtGH3 and OsGH3 genes had gone through purifying selective pressure for adaptive evolution. Motif analysis indicated that group-specific motifs may contribute to functional divergence across species and subgroups. Functional divergence analysis confirmed that subgroup-specific genes have experienced functional divergence during evolution, and elucidated the molecular mechanisms underlying their divergent functions. The tissue-specific expression analysis of SmGH3 AtGH3 and OsGH3 genes revealed that these genes might perform distinct functions in different tissues. This study performed a comprehensive bioinformatics analysis of the GH3 gene family, offering valuable information to further elucidate the functional roles of GH3 genes.